The Effect of Profitability, Capital Intensity, Debt to Asset Ratio On Tax Avoidance In Property Companies Listed On Indonesia Stock Exchange For The 2018-2020 Period - GAGOLA, Gabriela; KARAMOY, Herman; PUSUNG, Rudy (Journal of Governance, Taxation and Auditing, 2022)
Tax is the main indicator in the APBN because of the large percentage of tax revenue for maximum development in Indonesia. Taxes are obligations and expenses that reduce the company's net profit, this is contrary to the objectives of the entity. In 2020 the Director General of Taxes said that the implementation of tax avoidance resulted in losses to the state of up to 68.7 trillion per year. Therefore, many companies carry out tax avoidance measures. There are so many factors that can influence the occurrence of tax avoidance, including profitability, capital intensity, and debt to asset ratio. This study aims to determine the effect of the variables profitability, capital intensity, and debt to asset ratio on tax avoidance in property companies that are on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This study uses secondary data taken from the official website of the Indonesia Stock Exchange. The sample in this study used the nonprobability sampling which is purposive sampling technique, so that a sample of 17 companies was obtained with a total of 51 data. The analytical method used in this research is multiple linear regression analysis method. The results showed that profitability had no effect on tax avoidance, capital intensity had no effect on tax avoidance and debt to asset ratio had a significant positive effect on tax avoidance.